If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 1 = -2(3x + 10) Reorder the terms: 1 + -3x = -2(3x + 10) Reorder the terms: 1 + -3x = -2(10 + 3x) 1 + -3x = (10 * -2 + 3x * -2) 1 + -3x = (-20 + -6x) Solving 1 + -3x = -20 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 1 + -3x + 6x = -20 + -6x + 6x Combine like terms: -3x + 6x = 3x 1 + 3x = -20 + -6x + 6x Combine like terms: -6x + 6x = 0 1 + 3x = -20 + 0 1 + 3x = -20 Add '-1' to each side of the equation. 1 + -1 + 3x = -20 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -20 + -1 3x = -20 + -1 Combine like terms: -20 + -1 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) | | 2y+120=180 | | 4b=120-5t | | 2b+5=b+10 | | 52=(3x+2) | | 3(x+3)+x=2(x+3)-5 | | 9x^2+27x=7 | | y=3x^2-7x-1 | | 0.2(x-2)-0.4(x+2)=-0.2x-0.4 | | (R-2)3+6=38.85 |